Ethics and accuracy in scientific researches with emphasize on taxonomic works - Ghahari, H. (2010)
Research is one of those highly complex and subtle activities that usually remain quite unformulated in the minds of those who practise them. This is probably why most scientists think that it is not possible to give nay formal instruction in how to do research. Additionally, training in research must be largely self-training,preferably with the guidance of an experienced scientist in the handling of the actual investigation. Scientific research, which is simply the search for new knowledge, appeals especially to people who are individualists and their method vary from one person to another. A policy followed by one scientist may not be suitable for another, and different methods are required in different branches of science. However, there are some basic principles and mental techniques that are commonly used in most types of investigation, at least in the biological sphere. Honesty and morals are the first step in all scientific researches and a researcher must consider it in all stages of a scientific work. The role and importance of accuracy and honesty in taxonomy and systematic is more than other biological sciences. For having the honesty in scientific researches, learning the principals of ethics is needed for all the researchers and students. Therefore, this paper deals with the ethics in science and technology and also important comments on taxonomy.